Four-quadrant current-mode divider based on current conveyors - Pawarangkoon, Prajuab; Intaudom, Vuttikai; Kiranon, Wiwat (My University, 2004)
In this paper, a four-quadrant current-mode divider circuit is proposed The circuit employs only the current conveyors as active circuit elements and does not require external passive elements. It is therefore suitable for IC implementation. The circuit offers endurance on temperature variations. PSPICE simulation results are used to demonstrate the performance and accuracy of the proposed circuit. © 2004IEEE.